Interpretation Bias in Breast Cancer Survivors Experiencing Fear of Cancer Recurrence - Tuman, Malwina; Roberts, Kailey E.; Corner, Geoffrey; Beard, Courtney; Fadalla, Carol; Coats, Taylor; Slivjak, Elizabeth; Schofield, Elizabeth; Lichtenthal, Wendy G. (Frontiers in Psychology, 2021)
Introduction: Fear of cancer recurrence (FCR) is a prevalent and persistent challenge that many cancer survivors endure. While the role of interpretation bias, a tendency to perceive ambiguous situations as threatening, has been established in the onset and maintenance of FCR, few studies have examined cancer-related interpretation bias specifically. Grounded in the cognitive formulation of FCR, the current study aimed to fill this gap by investigating the relationship between cancer-related interpretation bias, FCR, and somatic symptoms, and examining whether bias mediates the relationship between somatic symptoms and FCR. Materials and methods: This study used baseline data from a randomized controlled trial of a cognitive bias modification intervention. Breast cancer survivors (n=110) provided demographic and medical background information as well as self-report measures of FCR and severity of somatic symptoms. A computer-based assessment of interpretation bias was used to measure cancer-related interpretation bias on several bias indices: percentage of cancer-related threat endorsement, and percentage of benign endorsement; mean reaction time (RT) for threat, and mean RT for benign endorsement. Results: Higher threat endorsement was linked to higher overall fear and emerged as a mediator of the relationship between overall somatic symptoms and overall fear. We also found that older age was related to longer benign endorsement RT. Conclusion: This study contributes understanding of factors related to cancer-related interpretation bias and provides evidence that bias may influence the relationship between somatic symptoms and FCR in cancer survivors.